Optimal Graph Algorithms on a Fixed-Size Linear Array - DOSHI, K. A; VARMAN, P. J (IEEE transactions on computers, 1987)
Parallel algorithms for computing the minimum spanning tree of a weighted undirected graph, and the bridges and articulation points of an undirected graphs on a fixed-size linear array of processors are presented. For a graph of n vertices, the algorithms operate on a linear array of p processors and require O(n2/p) time for all p, 1 ≤ p ≤ n. In particular, using n processors the algorithms require O(n) time which is optimal on this model. The paper describes two approaches to limit the communication requirements for solving the problems. The first is a divide-and-conquer strategy applied to Sollin's algorithm for finding the minimum spanning tree of a graph. The second uses a novel data-reduction technique that constructs an auxiliary graph with no more than 2n − 2 edges, whose bridges and articulation points are the bridges and articulation points of the original graph.